CD19 -targeted CAR T therapy treating hematologic malignancies: hidden danger is the next neighbor to security? - Ye, Xueshuai; Ge, Min; Tan, Mengtian; Wu, Yongqiang; Zhang, Haiqiang; Fu, Zexian (Frontiers in Immunology, 2025)
CD19-targeted chimeric antigen receptor (CAR) T-cell therapy has achieved marvelous results in the treatment of patients with relapsed and/or refractory B-cell lymphomas, B-cell acute lymphoblastic leukemia, and multiple myeloma. As a new treatment method that has changed the existing treatment paradigm, there has been a short time from its emergence to FDA approval. However, with the increasing number of cases and the passage of time, hidden problems have gradually been exposed. In this review, we summarize the short- and long-term toxicity, such as secondary T-cell tumors and lethal CAR tumors, of patients with hematologic malignancies treated with CD19-CAR-T cells, including cytokine release syndrome (CRS), ICANS, and secondary malignancies with low occurrence rates but high mortality, such as secondary T cell tumors and lethal CAR tumors, which may be related to the gene modification mechanism of viral vectors currently approved for CAR-T cells. We also discuss potential investigational strategies designed to improve the safety of CAR-T-cell therapy.